Analisis Prediksi Kebangkrutan pada Perusahaan Manufaktur Sub Sektor Food & Beverages Yang Terdaftar di Bursa Efek Indonesia: Menggunakan Model Altman, Springate, dan Grover - Widia Nasmi; Mayar Afriyenti (Universitas Negeri Padang, 2021)
The objective of this research is to determine (1) the prediction of bankruptcy of manufacturing companies in the food and beverages sub-sector listed on the Indonesia Stock Exchange by using the Altman, Springate and Grover models in the 2016 to 2019 period, and (2) to find out the differences in the results of bankruptcy predictions, and also to determine the level of accuracy of the five models in predicting bankruptcy. Sampling method used Purposive Sampling with some criterias which produce 14 samples of food and beverages firms for 5 years of data observation. The results indicate that, first, by using the Altman models, it is predicted that two companies will experience bankruptcy. Altman model and Grover model predict three companies to go bankrupt, while the Springate model predicts four companies to go bankrupt. Second, there is no significant difference between the Altman, Springate and Grover models in predicting the bankruptcy rate of food and beverages sub-sector companies listed on the Indonesia Stock Exchange. Third, the Springate model is a model that has the highest level of accuracy in predicting the bankruptcy of the food and beverages sub-sector, which has an accuracy rate of 92.86%.